Introduction of triploidy in ikan Baung,Mystus nemurus using temperature shock - Rossita Hj.Shapawi (Terengganu: Kolej Universiti Terengganu, 2014)
A study was carried out to investigate the possibility o f inducing triploid in ikan baung, M nemurus with temperature shocks (cold and heat). The eggs were subjected to cold (0, 2, 5 and 7°C at 2, 5, 7 and 10 minutes duration) and heat (35, 38, 40 and 42°C at 05, 1, 1.5 and 2 minutes duration) water temperature shock, 2 minutes after fertilization.